Psalms 90–106: book four and the Covenant with David - Gillingham, S (Berghahn Books, 2015)
The whole Psalter could be seen as a second Torah, whose five books are witness to the making, dissolution and renewal of the covenant with David. This article looks at Book Four of that story (Psalms 90–106), where the figure of Moses and the traditions of the Exodus are prominent and create an alternative vision to the covenant with David which is under threat (Psalm 89). These seventeen psalms comprise four collections (90–92, 93–100, 101–103, 104–106). By focusing on later Jewish and Christian reception of each psalm, the article shows how Jewish tradition maintains the earlier emphases on Moses and pre-Davidic traditions, whilst Christian tradition interprets them after the time of David, through the person of Christ. However, the article demonstrates that each tradition also recognizes a universal theology throughout Book Four: God as refuge in 90–92, God's cosmic rule in 93–100, God's mercy in suffering in 101–103, and God as Creator and Redeemer in 104–106.